2003
DOI: 10.1006/viro.2002.1740
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RNA Packaging in Wild-Type and Mosaic Protein Capsids of Flock House Virus Using Recombinant Baculovirus Vectors

Abstract: Flock house virus (FHV) is a small icosahedral insect virus of the family Nodaviridae. Its genome consists of two positive-sense RNA molecules, RNA1 (replicase gene) and RNA2 (coat protein gene), which are encapsidated into a single virion. Expression of coat protein in Sf21 cells using a baculovirus vector results in formation of virus-like particles (VLPs) whose capsids are structurally indistinguishable from native virions. However, RNA packaging is not specific for RNA2, the coat protein message. Using rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 29 publications
4
49
0
Order By: Relevance
“…This conclusion is consistent with the finding that synthetic FHV VLPs which were examined by X-ray scattering at low resolution (28) appeared to have RNA structure similar to that of wt FHV particles analyzed by cryoEM. Like the PaV VLPs, those from FHV contained predominantly heterologous RNAs (15,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This conclusion is consistent with the finding that synthetic FHV VLPs which were examined by X-ray scattering at low resolution (28) appeared to have RNA structure similar to that of wt FHV particles analyzed by cryoEM. Like the PaV VLPs, those from FHV contained predominantly heterologous RNAs (15,24).…”
Section: Discussionmentioning
confidence: 99%
“…FHV VLPs that contained mainly nonviral RNA (15,24) were more sensitive to protease digestion than wt particles, indicating that the authentic RNA plays a stabilizing role that is not fulfilled by heterologous RNAs (1). It is not yet known whether this difference is specifically related to the sequences, secondary structures, sizes, or other properties of the genomic RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of DNA transfer vectors for the generation of recombinant baculoviruses AcR1␦ and AcR2␦ with the BacPAK expression system kit (BD Biosciences) was previously described (13). These vectors contain the cDNA of FHV RNA1 and RNA2, respectively, with the hepatitis delta virus (HDV) ribozyme sequence (22) (2), in which the cDNA of RNA1 is fused to the HDV ribozyme sequence at its 3Ј end, was utilized.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that FHV replication can be initiated in Sf21 cells from recombinant baculovirus vectors (13). Specifically, we demonstrated that the coinfection of Sf21 cells with baculoviruses containing the cDNA for RNA1 and RNA2 launches self-directed RNA replication that leads to the formation of progeny FHV particles.…”
mentioning
confidence: 99%